P-wave dispersion in patients with rheumatic mitral stenosis - Rezaian, Gholam Reza (Pulsus Group Inc, 2007)
It has previously been shown that maximum P-wave duration and P-wave dispersion in 12-lead surface electrocardiogram (ECG) are significantly increased in patients prone to developing atrial fibrillation. Because patients with mitral stenosis (MS) are also susceptible to developing atrial fibrillation, the present study was carried out to determine whether maximum P-wave duration and P-wave dispersion are prolonged in MS patients during normal sinus rhythm. In addition, the correlation between these P-wave variables and the left atrial size, transmitral valve gradient and mitral valve area were determined. Fifty consecutive patients (40 women and 10 men; mean age 35.76±6.59 years) with MS who were in normal sinus rhythm, and a control group of 50 age- and sex-matched healthy persons were studied. A 12-lead ECG was obtained for each subject. All ECGs were scanned through a Cannon scanner at 300 dpi and saved as images in a personal computer. The minimum and maximum P-wave durations, as well as P-wave dispersion, were subsequently calculated. In addition, all patients were evaluated by echocardiography to measure the left atrial size, transmitral valve gradient and mitral valve area by planimetry. The P-wave parameters were compared between the two groups and the correlation between these parameters and the echocardiographic variables were determined in patients with MS. The most important findings included a significant prolongation of maximum P-wave duration in patients with MS compared with controls (P<0.001), and a strong correlation between the maximum P-wave duration and left atrial size (r=0.505, P<0.001), transmitral valve gradient (r=0.371, P=0.01) and a significant negative correlation with mitral valve area (r=−0.379, P=0.007). There was no correlation between the P-wave dispersion and echocardiographic parameters.